PENGARUH SOCIAL MEDIA MARKETING, ELECTRONIC WORD OF MOUTH, DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PRODUK EMINA COSMETICS DI KABUPATEN KUNINGAN - Martiani, Evita; Harjadi, Dikdik; Akbar, Ilham (Jurnal Bina Bangsa Ekonomika, 2025)
This study aims to determine the influence of social media marketing, electronic word of mouth and brand image on purchasing decisions. The method used in this research is a descriptive verification method with a quantitative approach. The population in this study was users of Emina Cosmetics in Kuningan with a sample of 100 respondents. The sampling technique uses purposive sampling. This research instrument is in the form of a questionnaire in a google form that is distributed directly to respondents. Data processing techniques use tests of validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linier regression analysis and coefficient of determination with the help of IBM SPSS version 25 application. The research results showed that (1) social media marketing, electronic word of mouth and brand image have a significant effect on purchasing decisions. (2) social media marketing has a positive and significant effect on purchasing decisions. (3) electronic word of mouth has a positive and significant effect on purchasing decisions. (4) brand image has a positive and significant effect on purchasing decisions. Keywords : Social Media Marketing, Electronic Word of Mouth, Brand Image, Purchasing Decisions